4. ANALISIS HUBUNGAN DIPLOMATIK INDONESIA-BRASIL TERHADAP KEBIJAKAN HUKUMAN MATI KEPADA DRUG TRAFFICKER DI INDONESIA (2009-2015) - Dewi, Widya Sarah; Utomo, Tri Cahyo; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Worldwide illegal drug trafficking has been constantly increasing. Many countries believethat drug crimes need a special penalization to give a deterrent effect to the perpetrators,one of which is in the form of capital punishment. Indonesia is one of the countries thathas been placing death penalty to the drug users as well as the traffickers. This widelycontroversial approach has been equally applied to many offenders regardless of theirorigins; locals and foreigners, including recently to the Brazilian drug traffickers. Thisresearch discusses the influence of Indonesian death penalty policy to the Brazilians drugtraffickers and how it effects the relations of Indonesia and Brazil. This study found thatthe death sentence policy in Indonesia has made quite an impact to the bilateral relations ofBrazil and Indonesia, where it particularly affects several aspects of economy, military,and especially political relations of the two countries. This research is carried out by usingdescriptive-explanative and qualitative method, focusing on the process and the actualevent of the case gathered from a number of sources and data. This study incorporates theframework of rational choice theory of the decision making policy as the conceptual basisof the research.